The principal from the black lagoon - Thaler, Mike, 1936-; Lee, Jared D. (New York : Scholastic, 1993)
A humorous story about a young boy who is sent to the principal's office. Along the way he imagines just how bad the visit will be.
In title: The word "Teacher" is crossed through with the word "Principal" written above it.
2.3
K-3
Keywords: Elementary school principals -- Juvenile fiction; Schools -- Juvenile fiction; School children -- Juvenile fiction; School principals -- Fiction; Schools -- Fiction; Humorous stories; Humorous stories; School stories